The Influence of Sports Events on Tourists’ Destination Choice Behaviour - Yingying Gong (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This study conducted to examine the influence of sports events on tourists' destination choice behaviour in China. The questionnaire was distributed both online and offline in the area surrounding City-A. The author through personal networks, including family and friends, as well as via WeChat group emails primarily disseminated online questionnaires. The findings reveal that 57.8% of respondents expressed a greater likelihood of attending large sports events, while 59.9% indicated an increased intention to travel to City-A in the future. The occurrence of large-scale sports events has played a significant role in establishing City A’s brand and has contributed to fostering a sports-oriented cultural environment, which is appealing to tourists. The study also highlights that the decision-making process regarding tourists' destination choices influenced by the presence of large-scale sports events, affecting tourists' behavioural patterns in selecting destinations.